2019
DOI: 10.3389/fonc.2019.01429
|View full text |Cite
|
Sign up to set email alerts
|

Latin American Study of Hereditary Breast and Ovarian Cancer LACAM: A Genomic Epidemiology Approach

Abstract: Purpose: Hereditary Breast and Ovarian Cancer (HBOC) syndrome is responsible for ∼5-10% of all diagnosed breast and ovarian cancers. Breast cancer is the most common malignancy and the leading cause of cancer-related mortality among women in Latin America (LA). The main objective of this study was to develop a comprehensive understanding of the genomic epidemiology of HBOC throughout the establishment Oliver et al. Latin American HBOC Study of The Latin American consortium for HBOC-LACAM, consisting of special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 58 publications
5
35
1
Order By: Relevance
“…However, this mutation was not seen in the given to BRCA1 mutations c.212+1G>A and BRCA1 c.799delT, which were the most prevalent within our study population. These two mutations were also seen once each in the 19 Guatemalan patients included in Oliver et al [6]. To the best of our knowledge, this is the largest genetic study of Central American breast cancer.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, this mutation was not seen in the given to BRCA1 mutations c.212+1G>A and BRCA1 c.799delT, which were the most prevalent within our study population. These two mutations were also seen once each in the 19 Guatemalan patients included in Oliver et al [6]. To the best of our knowledge, this is the largest genetic study of Central American breast cancer.…”
Section: Discussionmentioning
confidence: 68%
“…documented that Latin American women referred for genetic testing have equal or higher rates of BRCA1 and BRCA2 mutations (15%) as other groups [4]. The frequency and spectrum of hereditary cancer gene mutations have been described in Latin American and US Hispanic populations [5][6][7][8]. However, cancer disparities among US Hispanic subgroups may be further masked because they tend to be aggregated as a monolithic group in epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…In our study of 664 breast cancer patients from Guatemala, 11% (73/664) were found to carry pathogenic mutations in high and medium penetrance breast cancer susceptibility genes. Guatemalan women have a higher ratio of deleterious BRCA1/BRCA2 mutations (2.8) than US Hispanic women or other Latin American populations [3][4][5][6]. The higher BRCA1 mutation rate is attributable to the high prevalence of the c.212 + 1G > A and c.799delT mutations.…”
Section: Discussionmentioning
confidence: 98%
“…These two mutations are not known to be common in the United States and other Latin American countries, suggesting that they are founder mutations in the Guatemalan population [3,6,8]. A previous study of 222 patients across four Latin American countries (Argentina, Colombia, Guatemala, and Mexico) had described a prevalence of pathogenic variants at 17% (38/222); however, if only high and medium penetrance breast cancer genes are included that percentage drops to 13% (29/222) overall and 11% (2/19) in Guatemala [6]. The BRCA mutation prevalence among Latinas in the US is 1.2-4.9% in cohorts of unselected patients with breast cancer and a separate study of 1054…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation